СТАНОВЛЕННЯ РАДЯНСЬКОЇ ПОЛІТИЧНОЇ СИСТЕМИ (Zaporizhzhia Historical Review, 2021)
In the article the author highlights formation process of Soviet political system and its major periods in 1905-1938. He depicts specific role of Party, councils, trade unions and force structures in this system, their functions in it. The conclusion is made as to “Stalin’s revolution from the top” practicability in conditions of the end of 1920-1930s.